Direct Access to α‐Aminosilanes Enabled by Visible‐Light‐Mediated Multicomponent Radical Cross‐Coupling. (17th September 2021) - Yu, Xiaoye; Daniliuc, Constantin G.; Alasmary, Fatmah Ali; Studer, Armido
Abstract: α‐Aminosilanes are an important class of organic compounds that show biological activity. In this communication, a new approach to α‐aminosilanes that utilizes photoredox catalysis to enable three‐component coupling of organo(tristrimethylsilyl)silanes with feedstock alkylamines and aldehydes is presented. A wide range of highly functionalized α‐aminosilanes can be obtained in good yields under mild conditions. Both primary amines and secondary amines are compatible with this transformation. Moreover, optically pure α‐aminosilanes are accessible by using chiral amines. Mechanistic studies indicate that reactions proceed through radical/radical cross‐coupling of silyl radicals with α‐amino alkyl radicals. Abstract : Direct cross‐coupling of organo(tristrimethylsilyl)silanes with alkylamine and aldehyde feedstocks has been achieved. A wide range of highly functionalized α‐aminosilanes can be obtained with generally good yields and optically pure α‐aminosilanes are accessible with excellent stereocontrol. This method provides a novel disconnection strategy for the synthesis of a diverse range of α‐aminosilanes.